Amateur soccer players and the phenomenon of motivation - Papanikolaou, Z.; Patsiaouras, A. (The Sport Journal, 2014)
The relationship between various types of psychological and social motivation in amateur soccer players was examined in this paper.Twenty eight males and 14females who participated in this study regularly engaged in soccer. The amateur soccer players ranged in experience from beginning to advanced soccer, with the majority self-reporting at an intermediate level. Subjects were given Butt`s Short Scales for the Measurement of Sport Motivation. Males and females soccer players scored similarly on the aggression scale. Female amateur soccer players scored significantly higher on the conflict scale than did male soccer players. Identical means were found for males and females on the competence scale. There were no differences found between males and females on the motivational scales for competition and cooperation. Due to the small number of subjects who have participated, general conclusions can only be made with great caution.